Rapid Induction and Maintenance of Virus-Specific CD8+ TEMRA and CD4+ TEM Cells Following Protective Vaccination Against Dengue Virus Challenge in Humans - Graham, Nancy; Eisenhauer, Phil; Diehl, Sean A.; Pierce, Kristen K.; Whitehead, Stephen S.; Durbin, Anna P.; Kirkpatrick, Beth D.; Sette, Alessandro; Weiskopf, Daniela; Boyson, Jonathan E.; Botten, Jason W. (Frontiers in Immunology, 2020)
Dengue virus (DENV) is a mosquito-borne flavivirus that causes serious human disease. The current lack of an effective vaccine to simultaneously protect against the four serotypes of DENV in seronegative individuals is a major unmet medical need. Further, the immunological basis for protective immunity in the setting of DENV infection or vaccination is not fully understood. Our team has developed a live attenuated tetravalent dengue virus vaccine that provides complete protection in a human model of dengue virus challenge. The goal of this study was to define, in the context of protective human vaccination, the quality of vaccine-induced DENV-specific CD8+ and CD4+ T cells and the temporal dynamics associated with their formation and maintenance. Multifunctional, DENV-specific CD8+ and CD4+ T cells developed eight to 14 days after vaccination and were maintained for at least six months. Virus-specific CD8 T+ cells were a mixture of effector memory T cells (TEM) and effector memory T cells re-expressing CD45RA (TEMRA), with TEM cells predominating until day 21 post-vaccination and TEMRA cells thereafter. The majority of virus-specific CD4+ T cells were TEM with a small fraction being TEMRA. The frequency of virus-specific CD8+ and CD4+ T cells were further skewed to the TEMRA phenotype following either a second dose of the tetravalent vaccine or challenge with a single serotype of DENV. Collectively, our study has defined the phenotypic profile of antiviral CD8+ and CD4+ T cells associated with protective immunity to DENV infection and the kinetics of their formation and maintenance.